DEVELOPMENT OF COMPANIES AND INNOVATIVE BUSINESS MODELS - Baizhanova L.B; Kunanbaeva D.A (Academic Journal of Physical and Chemical Sciences, 2019)
For managing the innovative development of an enterprise, the description of its business model is important and timely. This article outlines the approach to building a business model for the innovative development of industrial enterprises. An integrated business model is an important tool for the formalization and improvement of the company. The article discusses the general rules for creating an innovative business model: functions, enterprise mission, strategy, principles, types of innovative business models. In addition, it is noted that it is necessary to conduct research on the conditions that force one to switch from one type of business model to another.